Prediction of Pollutant Emissions from Bluff-Body Stabilised Nonpremixed Flames - Nelu Munteanu; Shokri M. Amzaini (Journal of Combustion)
Construction of a stable flame is one of the critical design requirements in developing practical combustion systems. Flames stabilised by a bluff-body are extensively used in certain types of combustors. The design promotes mixing of cold reactants and hot products on the flame surface to improve the flame stability. In this study, bluff-body stabilised methane-hydrogen flames are computed using the steady laminar flamelet combustion method in conjunction with the Reynolds-averaged Navier-Stokes (RANS) approach. These flames are known as Sandia jet flames and have different jet mean velocities. The turbulence is modelled using the standard k-ϵ model and the chemical kinetics are modelled using the GRI-mechanism with 325 chemical reactions and 53 species. The computed mean reactive scalars of interest are compared with the experimental measurements at different axial locations in the flame. The computed values are in reasonably good agreement with the experimental data. Although some underpredictions are observed mainly for NO and CO at downstream locations in the flame, these results are consistent with earlier reported studies using more complex combustion models. The reason for these discrepancies is that the flamelet model is not adequate to capture the finite-rate chemistry effects and shear turbulence specifically, for species with a slow time scale such as nitrogen oxides.